The linkage of SSR markers with bacterial wilt disease resistance in peanut - Thuy Linh, Ngo Thi; Tru, Nguyen Van; Bich Thuy, Le Thi; Thang, Nguyen Van; Van, Nguyen Thi; Viet, Nguyen Van (Academia Journal of Biology, 2016)
Bacterial wilt, caused by Ralstonia solanacerum Smith is one of the major diseases causing significant yield loss in peanut all over the world. Selection and evaluation of bacterial wilt resistant cultivars by traditional method are retrained because the effective transfer of disease resistant genes to hybrid line by traditional method is difficult and time consuming. Therefore, the application of molecular maker for selection and evaluation of bacterial wilt resistant cultivars in peanut is the most feasible method for controlling the disease. In this study, we presented the results on the use of 63 peanut cultivars and 60 SSR primers to indentify the linkage between molecular markers and bacterial wilt resistance. There were 31 bacterial wilt resistant cultivars in 63 peanut cultivars (49.21%). Twenty six primer pairs gave polymorphism with a total of 90 alleles. The number of alleles ranged from 2 to 6 alleles with an average of 3.46 locus/allele. The ratio of rare allele was 26.92% (seven rare alleles occurred at PM137, PM3, pPGSseq14A7, RN2F12, pPGSseq3F5, 7G2 and 16C6. The means of polymorphism information content were from 0.2955 (PM606 primer) to 0.7469 (TC1A02 primer) with an average of 0.5560. Three SSR markers, namely pPGPSeq3F05, GA161 and 7G2 were indentified to be linked to bacterial wilt resistance after association analysis by single marker analysis method. These markers could be useful for selection and evaluation of bacterial wilt resistance in peanut.